Hereditary thrombophilia as stroke aetiology in children: Three case report [Çocuklarda inme etiolojisinde doǧal inhibitör eksikliǧi: Üç olgu sunumu] - (:unkn) unknown (Kare Publishing, 2007)
Stroke, a rare condition during childhood, remains to be an important cause of mortality and morbidity. The etiology of stroke in children is different from adults and could be determined only in the half of the cases previously. However, hereditary thrombophilias and coagulation defects have been more commonly identified during last two decades and the importance of the hereditary thrombophilias in the etiology of stroke is better understood. Clarifying the etiology is important to predict the prognosis and prevent recurrences. We report here three patients with hereditary thrombophilias leading stroke and discuss the importance as well as the treatment and prophylaxis of hereditary thrombophilias.
Keywords: Factor V leiden; Heparin; Hereditary thrombophilia; Protein C; Protein S; Stroke